The Lambeth Early Onset (LEO) Team: randomised controlled trial of the effectiveness of specialised care for early psychosis. Issue 7474 (14th October 2004) - Craig, Tom K J; Garety, Philippa; Power, Paddy; Rahaman, Nikola; Colbert, Susannah; Fornells-Ambrojo, Miriam; Dunn, Graham
Abstract: Objective To evaluate the effectiveness of a service for early psychosis. Design Randomised controlled clinical trial. Setting Community mental health teams in one London borough. Participants 144 people aged 16-40 years presenting to mental health services for the first or second time with non-organic, non-affective psychosis. Interventions Assertive outreach with evidence based biopsychosocial interventions (specialised care group) and standard care (control group) delivered by community mental health teams. Primary outcome measures Rates of relapse and readmission to hospital. Results Compared with patients in the standard care group, those in the specialised care group were less likely to relapse (odds ratio 0.46, 95% confidence interval 0.22 to 0.97), were readmitted fewer times (β 0.39, 0.10 to 0.68), and were less likely to drop out of the study (odds ratio 0.35, 0.15 to 0.81). When rates were adjusted for sex, previous psychotic episode, and ethnicity, the difference in relapse was no longer significant (odds ratio 0.55, 0.24 to 1.26); only total number of readmissions (β 0.36, 0.04 to 0.66) and dropout rates (β 0.28, 0.12 to 0.73) remained significant. Conclusions Limited evidence shows that a team delivering specialised care for patients with early psychosis is superior to standard care for maintaining contact with professionals and for reducing readmissions to hospital. No firm conclusions can, however, be drawn owing to the modest sample size.